Kinerja Keuangan PT Charoen Pokphand Indonesia Tbk (CPIN) 2014-2025: Pendekatan Deskriptif dengan CR, ROE, PE Ratio, dan Dividend Yield - Fatkhiyah Rohmah; Reismaya Wanamertan Nugroho; Zulaikha Anugraheni (Journal of Livestock Science and Production, 2025)
This study analyzes the financial performance of PT Charoen Pokphand Indonesia Tbk (CPIN) from 2015 to 2024 using a descriptive approach through financial ratio analysis in the form of Current Ratio (CR), Return on Equity (ROE), Price to Earnings (PE) Ratio, and Dividend Yield (DY). The purpose of this study is to evaluate the company's financial performance before, during, and after the Covid-19 pandemic. This pandemic has had a significant impact on the global economy, including the agribusiness sector, which has affected the company's financial performance. The data used in this study were obtained from financial reports published by the company on the IDX website. The analysis results show that although CPIN experienced fluctuations in financial ratios due to the pandemic, the company showed a positive recovery after the pandemic. The company's liquidity (CR) and profitability (ROE) performance declined during the pandemic but increased again in the post-pandemic period. Meanwhile, the stock valuation ratio (PE Ratio) also showed fluctuations due to changes in market expectations regarding the company's performance.